LPA-primed astrocytes induce axonal outgrowth of cortical progenitors by activating PKA signaling pathways and modulating extracellular matrix proteins - Spohr, Tania Cristina Leite de Sampaio e; Dezonne, Rômulo Sperduto; Rehen, Stevens Kastrup; Gomes, Flávia Carvalho Alcantara (Frontiers in Cellular Neuroscience, 2014)
Lysophosphatidic acid (LPA) is one of the main membrane-derived lysophospholipids, inducing diverse cellular responses like cell proliferation, cell death inhibition, and cytoskeletal rearrangement, and thus is important in many biological processes. In the central nervous system (CNS), post-mitotic neurons release LPA extracellularly whereas astrocytes do not. Astrocytes play a key role in brain development and pathology, producing various cytokines, chemokines, growth factors, and extracellular matrix components that act as molecular coordinators of neuron–glia communication. However, many molecular mechanisms underlying these events remain unclear - in particular, how the multifaceted interplay between the signaling pathways regulated by lysophospholipids is integrated in the complex nature of the CNS. Previously we showed that LPA-primed astrocytes induce neuronal commitment by activating LPA1–LPA2 receptors. Further, we revealed that these events were mediated by modulation and organization of laminin levels by astrocytes, through the induction of the EGFR signaling pathway and the activation of the MAPK cascade in response to LPA (Spohr et al., 2008; Spohr et al., 2011). In the present work, we aimed to answer whether LPA affects astrocytic production and rearrangement of fibronectin, and to investigate the mechanisms involved in neuronal differentiation and maturation of cortical neurons induced by LPA-primed astrocytes. We show that PKA activation is required for LPA-primed astrocytes to induce neurite outgrowth and neuronal maturation and to rearrange and enhance the production of fibronectin and laminin. We propose a potential mechanism by which neurons and astrocytes communicate, as well as how such interactions drive cellular events such as neurite outgrowth, cell fate commitment, and maturation.